Redignifying utopia as an instrument of criticism - Castro, Felipe Araújo (Revista de Ciências do Estado, 2017)
The purpose of the present work is to explain the original positive meaning of the idea of Utopia and its uses, and then to critically analyze the process of discrediting the category in representations of mere unfeasible fantasies, above all, from modernity with the development and intensification of Science and technology in the context of capitalism.It is intended to emphasize the important contribution for the process of discrediting the utopian functions of the critique elaborated by Marx and Engels on the separation between utopian socialism and scientific socialism, highlighting the later reception and vulgarization of this critique by the economicist currents of Marxism. Finally, it is defended the utility and necessity of the rescue of utopia in contemporary times, making use of authors inserted in the critical theory and committed to the search for a new utopian spirit that redignifies its uses. In this context, the notion of concrete utopia of Ernst Bloch and his proposal of a new relationship between man and nature based on a technique of alliance are highlighted.